The study of promising secure information systems based on signal modeling - V. A. Sizov; D. M. Malinichev; Kh. K. Kuchmezov (Открытое образование (Москва), 2019)
The aim of the study is to increase the effectiveness of information security management through the use of 5G networks. The transition to the fifth-generation network does not solve the existing problems of information security and leads to the emergence of new threats. The main objective of each modulation method of signals is to ensure high bandwidth, proper transmission quality in a noisy communication channel, using the minimum amount of energy. One of the most effective indicators of increasing the level of information security in wireless networks is quadrature modulation, which is used in such networks as: LTE, WiMAX, McWill, DVB-T (T2), Wi-Fi and other radio access networks [1].One of the promising directions for the development of 5G networks is the use of higher frequency ranges, such as the range of millimeter waves (from 30 to 300 GHz) [2, 3]. A feature of the millimeter wave range is that they provide much wider spectral bands, making it possible to significantly increase the bandwidth in the channels. Thus, when studying prospective protected information systems based on the use of 5G network technology, it is advisable to use a simulation of the signals of the channel-level interaction of subscribers, which allows you to evaluate the basic security parameters at the physical level.Materials and research methods. Fifth generation networks will simultaneously look like any previous generation of mobile networks, and at the same time they will differ significantly from them – and there are a number of explanations that become more obvious if you think about how these changes affect the principles of user and equipment safety networks of the fifth generation.Widespread in the field of digital information transmission, including 5G networks, has received combinational modulation, called quadrature amplitude modulation.Multiposition signals have the greatest spectral efficiency, of which four-position phase modulation and sixteen-position quadrature amplitude modulation are most often used.The quadrature amplitude modulation is a kind of multi-position amplitude-phase modulation, in addition to the phase, the amplitude of the signal for a given type of modulation will also carry information. This leads to the fact that for a given frequency band the amount of transmitted information increases.A brief overview of the existing modulation approaches is presented OFDM (english. Orthogonal frequency-division multiplexing) [4, 5] systems and methods for forming solutions of signal modulation problems for building such systems/Results. Currently, OFDM technology is widely used in modern wireless Internet systems. High data transfer rates in OFDM systems are achieved using parallel information transfer over a large number of orthogonal frequency subchannels (subcarriers) [6].The method of synthesizing signal-code constructions with orthogonal frequency multiplexing provides for different scenarios for the use of semi-square modulation depending on the requirements for interception protection, as well as balancing between spectral and energy efficiency. This method can be used in two cases: with alternative and consistent transmission of signals. In the case of alternative transmission, only one of the four subcarriers is used during one channel interval. For efficient use of bandwidth, the proposed method involves the use of the spectrum of three other subcarriers for data transmission in D2D channels (this creates a connection between two user devices that are in close proximity), which allows you to further avoid interference between fixed channels and D2D communication channels.Findings. At present, 5G networks can be considered as one of the necessary components of the digital transformation and digital economy, while the main task in ensuring security in cellular communications is protection against eavesdropping. However, in the future world of smartphones and the Internet of things, in environments with a large number of mechanisms, the probability of listening is likely to fade into the background. Instead, you have to think about such things as data manipulation attacks, which, for example, can be used to command the mechanisms to perform certain actions (for example, open the door or take control of an unmanned vehicle). Mobile network operators, like consumer electronics manufacturers, will be able to offer “security as a service,” with the result that application providers will be able to apply additional levels of security over existing secure cellular network channels when transferring certain types of data. [7] Due to the better spectral density, the proposed signal conditioning method makes it possible to use prototypes of window functions with the best spatial localization properties without violating the orthogonality condition of the signal bases, and accordingly does not require the use of cyclic prefixes when generating the OFDM signal.